The Capability Approach and the Praxis of Development - Deneulin, S. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2006)
The book examines the extent to which Amartya Sen's conception of 'development as freedom' can be a guide for development policy. It argues that the theoretical foundations of the conception need to be expanded, and that it needs to give more attention to collective and historical dimensions if it is to address poverty effectively.